AN EARLY VALIDATION OF IMAGE PROCESSING TECHNIQUE FOR FLATNESS MEASUREMENT - Rima Zuriah Amdani; Eka Pratiwi; Nadya Larasati kartika; Muhammad Azzumar (Badan Standardisasi Nasional, 2019)
An experimental validation of flatness measurement based on image processing technique has been performed. The purpose of this study is to know the performance of the image processing technique in the flatness measurement. In addition, this technique will be used as development of current measurement technique that is performed manually. The advantage of using this method is that in the future the measurement system will run semi-automatically, so it can increase the capacity. This study is used 3 samples of optical flat with different in diameter (i.e. 25 mm, 45 mm, and 75 mm). The validation has been performed by comparing measurement results of the image processing technique and the manual technique through degree of equivalence evaluation. The error numbers based on the degree of equivalence criteria between the image processing technique and the manual technique for the flatness measurement of 25 mm, 45 mm, and 75 mm are 0.02, 0.09, and 0.11 respectively. According to those error numbers, the image processing technique measurement results is in agreement with the manual technique. Moreover, those results have validated that the image processing technique has good performance and can potentially be implemented to the flatness measurement.